Vibration suppression analysis and experimental test of additional constrained damping layer in space science experiment cabinet. (2nd February 2021) - Luo, Haitao; Guo, Siwei; Yu, Changshuai; Fu, Jia; Wang, Haochen; Liu, Guangming; Luo, Zhong
Aiming at the problem that the vibration of the space science experimental cabinet is too large during the launch phase of the rocket, the viscoelastic constrained damping layer is used to suppress the vibration. Firstly, to explore the vibration suppression mechanism of the constrained damping layer, the dynamic model of the constrained damping layer is established and the modal loss factor is calculated. Secondly, the influence of the modulus, material thickness, and the position and the area of the damping layer on the loss factor of the structure is analyzed. Finally, the simulation and experiment methods are used to calculate and verify the space science experiment cabinet with additional constrained damping layer. The results show that the viscoelastic constrained damping can effectively reduce the vibration level of the space science experiment cabinet, and the acceleration response in the resonance region is reduced by more than 56%. The viscoelastic constrained damping structure is simple and easy to realize, which can suppress the vibration of the space payload design is of great significance.